Adenoviral expression of TDP‐43 and FUS genes and shRNAs for protein degradation pathways in rodent motoneurons in vitro and in vivo. Issue 1 (12th August 2013) - Watabe, Kazuhiko; Akiyama, Keiko; Kawakami, Emiko; Ishii, Tomohiro; Endo, Kentaro; Yanagisawa, Hiroko; Sango, Kazunori; Tsukamoto, Masami
<x xml:space="preserve">Abstract</x> Formation of cytoplasmic aggregates in neuronal and glial cells is one of the pathological hallmarks of amyotrophic lateral sclerosis (ALS). Mutations in two genes encoding transactivation response (TAR) DNA‐binding protein 43 (TDP‐43) and fused in sarcoma (FUS), both of which are main constituents of cytoplasmic aggregates, have been identified in patients with familial and sporadic ALS. Impairment of protein degradation machineries has also been recognized to participate in motoneuron degeneration in ALS. In the present study, we produced recombinant adenovirus vectors encoding wild type and mutant TDP‐43 and FUS, and those encoding short hairpin RNAs (shRNAs) for proteasome (PSMC1), autophagy (ATG5), and endosome (VPS24) systems to investigate whether the coupled gene transductions in motoneurons by these adenoviruses elicit ALS pathology. Cultured neurons, astrocytes and oligodendrocytes differentiated from adult rat neural stem cells and motoneurons derived from mouse embryonic stem cells were successfully infected with these adenoviruses showing cytoplasmic aggregate formation. When these adenoviruses were injected into the facial nerves of adult rats, exogenous TDP‐43 and FUS proteins were strongly expressed in facial motoneurons by a retrograde axonal transport of the adenoviruses. Co‐infections of adenovirus encoding shRNA for PSMC1, ATG5 or VPS24 with TDP‐43 or FUS adenovirus enhanced cytoplasmic aggregate formation in facial motoneurons, suggesting that impairment of protein degradation pathways accelerates formation of TDP‐43 and FUS‐positive aggregates in ALS.